Sifat Listrik komposit yang difabrikasi dari carbon-phenol formaldehyde - Belyamin; Agus Edy Pramono; Yohannes PatrickR Patrick; Nanik Indayaningsih Indayaningsih (MBI, 2023)
This research aimed to create composites of carbon-phenol formaldehyde (PF) using carbonated rice husks as fillers. The composites showed electrical conductivity that increased with carbon content and decreased electrical resistance. The composites were evaluated for their physical, and electrical properties. The results showed that increasing PF content resulted in higher density but lower porosity, making the composites heavier. Specimens with 80% carbon weight and 20% PF weight produce an electrical conductivity of 0.055 [S/cm], while those with 70% carbon weight and 30% PF weight produce an electrical conductivity of 0.039 [S/cm]. Specimens with 60% carbon weight and 40% PF weight generate an electrical conductivity of 0.013 [S/cm].